Fkbp52 Regulates Androgen Receptor Transactivation Activity and Male Urethra Morphogenesis - Chen, Hanying (American Society for Biochemistry and Molecular Biology, 2010)
Hypospadias is a common birth defect in humans, yet its etiology and pattern of onset are largely unknown. Recent studies have shown that male mice with targeted ablation of FK506-binding protein-52 (Fkbp52) develop hypospadias, most likely due to actions of Fkbp52 as a molecular co-chaperone of the androgen receptor (AR). Here, we further dissect the developmental and molecular mechanisms that underlie hypospadias in Fkbp52-deficient mice. Scanning electron microscopy revealed a defect in the elevation of prepucial swelling that led to the onset of the ventral penile cleft. Interestingly, expression of Fkbp52 was highest in the ventral aspect of the developing penis that undergoes fusion of the urethral epithelium. Although in situ hybridization and immunohistochemical analyses suggested that Fkbp52 mutants had a normal urethral epithelium signaling center and epithelial differentiation, a reduced apoptotic cell index at ventral epithelial cells at the site of fusion and a defect of genital mesenchymal cell migration were observed. Supplementation of gestating females with excess testosterone partially rescued the hypospadic phenotype in Fkbp52 mutant males, showing that loss of Fkbp52 desensitizes AR to hormonal activation. Direct measurement of AR activity was performed in mouse embryonic fibroblast cells treated with dihydrotestosterone or synthetic agonist R1881. Reduced AR activity at genes controlling sexual dimorphism and cell growth was found in Fkbp52-deficient mouse embryonic fibroblast cells. However, chromatin immunoprecipitation analysis revealed normal occupancy of AR at gene promoters, suggesting that Fkbp52 exerts downstream effects on the transactivation function of AR. Taken together, our data show Fkbp52 to be an important molecular regulator in the androgen-mediated pathway of urethra morphogenesis.